Improved Thermophysical Properties of Developed Ternary Nitrate-Based Phase Change Material Incorporated with MXene as Novel Nanocomposites - I, Samylingam; Aslfattahi, Navid; K., Kadirgama; Mahendran, Samykano; L., Samylingam; R., Saidur (Tech Science Press, 2021)
In this study, nanocomposite of ternary nitrate molten salt induced with MXene is developed. LiNO3-NaNO3- KNO3 with wt% of 35:12:53 and 35:10:55 are produced and doped with MXene in the wt% of 0.2, 0.5, 1.0, and 1.5. FTIR result indicates the composites had no chemical reaction occurred during the preparation. UV-VIS analysis shows the absorption enhancement with respect to the concentration of MXene. Thermogravimetric analysis (TGA) was used to measure the thermal stability of the LiNO3-NaNO3-KNO3 induced with MXene. The ternary molten salts were stable at temperature range of 600–700°C. Thermal stability increases with the addition of MXene. 1.5 wt% of MXene doped with LiNO3-NaNO3-KNO3 with wt% 35:10:55 and 35:12:53, increases the thermal stability from 652.13°C to 731.49°C and from 679.82°C to 684.57°C, respectively. Using thermophysically enhanced molten salt will increase the efficiency of CSP